Cassava waste (stem and leaf) analysis for reuse - Soares, Isabela Simões [UNESP]; Perrechil, Fabiana; Grandis, Adriana; Pagliuso, Débora; Purgatto, Eduardo; de Oliveira, Luciana Alves; Cavalari, Aline Andreia (Elsevier, 2024)
Cassava is an important crop for developing countries. In addition to its roots, the leaves are rich in proteins and minerals that could substantially supplement diets if treated properly, as they contain some anti-nutritional factors. Plant residues can be used as raw material in the food industry and as bioenergy. This work aimed to characterize the profile of macronutrients and polysaccharides in leaves and stems of two cassava clones generated by the breeding program (classical genetic improvement/grafting) of Embrapa Mandioca & Fruticultura. Dehydrated and crushed leaves and stems evaluated for chemical composition, in addition to the determination of cyanogenic compounds and polysaccharides. Macronutrients were similar between the two studied clones in stem and leaves. Moisture values of approximately 8.5 %, a protein content of 20.44 % and small amounts of soluble sugars and starch, overlapping the fiber content that approaches 25 %, containing a low concentration of pectins but high levels of lignin, which gives the material potential for saccharification mainly in the trunk. The results also showed that these foods, used in animal feed, represent potential raw materials for the food and bioenergy industry with high added value.
Keywords: Cyanogenic compounds; Residues, carbohydrates, major components